Controlled biosynthesis of curdlan oligosaccharides with tunable degree of polymerization and their prebiotic effects on gut microbiota - Yaping Pan; Yuying Wang; Zhilei Liu; Tong Liang; Zepeng Chang; Qingyu Wang; Qijun Pan; Yun Jiang; Zhitao Li; Minjie Gao (Bioresource Technology, 2026)

Combined CO₂ and topographic uplift forcing on vegetation and climate change in the North China Plain since ∼6.5 Ma - Wei Liu; Likang Wang; Zhenjing Yang; Dianbao Chen; Dexuan Chen; Yaping Li; Xiaozhong Huang; Yunfa Miao; Baotian Pan (Global and Planetary Change, 2026)

The alkaloid-rich extract of Piper sintenense Hatusima alleviates gouty inflammatory response via Nrf2-mediated antioxidant induction - Zhiren Yao; Yu Su; Yaping Huang; Can Hu; Ke Pan; Jian Zhang; Guoqing Zhao; Lei Wang; Zhiqi Yin (Inflammopharmacology, 2026)

BAMBI modulates proliferation, apoptosis, and hormone secretion in Jinding duck granulosa cells - Li Li; Xiaopan Liu; Changtao Liu; Chengfu Pan; Linli Zhang; Qingwu Xin; Zhongwei Miao; Liang Huang; Yuwei Li; Yaping Zhang; Qinlou Huang; Nenzhu Zheng; et al. (Animal Reproduction Science, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Simultaneously promoting gellan lyase expression and gellan oligosaccharide production by gellan gum co-feeding during Pichia pastoris fermentation - Tong Liang; Yuying Wang; Feiyang Duan; Yaping Pan; Zepeng Chang; Qijun Pan; Yun Jiang; Zhitao Li; Minjie Gao (Systems Microbiology and Biomanufacturing, 2026)

Efficient proton exchange membrane water electrolysis by activating “inactive” catalysts - Yaping Pan; Xinlong Zhuang; Kejie Lao; Linrui Wen; Guang Deng; Hailong Wang; Hanchun Wang; Hua Bing Tao; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Boosting arsenic removal with metastable Fe2+/Mn3+ redox process in MnFe2O4/rGO composites for high capacity and stability - Tao Zhang; Shengjia Ma; Du Chen; Qingsheng Wu; LiKun Pan; Jiang Xu; Yaping Zhao (Journal of Hazardous Materials, 2025)

An ultrathin conformal layer of dry-coated Li+-conductive glass–ceramic for single-crystalline nickel-rich cathode towards all-solid-state lithium batteries - Yaping Wang; Jianxiang Ding; Xiong Xiong Liu; Mufan Cao; Min Gao; Long Pan; ZhengMing Sun (Chemical Engineering Journal, 2025)

Conceptual design of an improved ammonia refining process for coal chemical wastewater - Jingtao Guo; Chao Pan; Yaping Liu; Xingming Jin; Bingxiao Feng; Hengjun Gai (Journal of Water Process Engineering, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Well-cushioned and highly-elastic aerogel for multifunctional intelligent transportation packaging - Ruiming Liu; Xiaosen Pan; Zijun Mao; Zijun Xu; Yaping Zhu; Pan Xue; Zhengjian Zhang; Hongbin Liu; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2024)

Efficient separation of cresol isomers using azeotropic coupling pressure-swing distillation: From separation mechanism to process integration - Chao Pan; Jingtao Guo; Yaping Liu; Bingxiao Feng; Guoxuan Li; Hengjun Gai; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2024)

Chemically tailored molecular surface modification of bamboo pulp fibers for manipulating the electret performance of electret filter media - Chunxia Pang; Huanhuan You; Sijie Lei; Fan Su; Lili Liang; Zhanguo Li; Xiaoyan Lin; Yaping Zhang; Hao Zhang; Xunhai Pan; Yang Hu (Carbohydrate Polymers, 2024)

Oxidative esterification of 5-hydroxymethylfurfural to dimethyl 2,5-furandicarboxylate over Au-supported poly(ionic liquid)s - Yaping Liu; Chao Pan; Xiaomin Qiu; Xianjie Li; Hengjun Gai; Meng Xiao; Tingting Huang; Quanhong Zhu; Hongbing Song (Fuel, 2024)

Nanocellulose based ultra-elastic and durable foams for smart packaging applications - Yang Liu; Yaping Zhu; Zijun Xu; Xin Xu; Pan Xue; Hong Jiang; Zhengjian Zhang; Meng Gao; Hongbin Liu; Bowen Cheng (Carbohydrate Polymers, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

A Review of Electrochemical Treatment Processes of Leachate Membrane Concentrate - Peixin Tang; Xu Ren; Zhicheng Pan; Meng Shen; Danni Peng; Yucheng Liu; Yaping Zhong; Yumei Peng; Xin Peng (Water, Air, & Soil Pollution, 2024)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

A step closer to real practice: Integrated tandem photocatalysis-biofilm process towards degradation of crude oil - Xin Hu; Yaping Pan; Shanshan Zhao; Feifei Zhang; Fengshu Li; Zhe Li; Haoshuai Li; Yiming Li; Jinren Lu; Xiaolong Yang; Mutai Bao (Journal of Environmental Management, 2023)

Uncovering the dynamic evolution of microbes and n-alkanes: Insights from the Kuroshio Extension in the Northwest Pacific Ocean - Xin Hu; Xinping Wang; Shanshan Zhao; Lixin Cao; Yaping Pan; Fujuan Li; Fengshu Li; Jinren Lu; Yiming Li; Guodong Song; Honghai Zhang; Peiyan Sun; et al. (Science of The Total Environment, 2023)

The structure, characterization and dual-activity of exopolysaccharide produced by Bacillus enclensis AP-4 from deep-sea sediments - Xin Hu; Fengshu Li; Xiuli Zhang; Yaping Pan; Jinren Lu; Yiming Li; Mutai Bao (Frontiers in Marine Science, 2022)
In recent years, the exopolysaccharide (EPS) produced by deep-sea bacteria has attracted the interest of various researchers. In the present study, we have explored the properties and structure of a novel exopolysaccharide (called BPS) produced by Bacillus enclensis AP-4 from deep-sea sediments. The maximum yield of BPS was 4.23 ± 0.17 g L −1 in a 2216E modified medium. 1 H NMR studies of the purified BPS displayed α and β-configuration sugar residues, including mannose, glucosamine, glucose, galactose, and xylose in a molar ratio of 1.00: 0.09: 0.04: 0.09: 0.07. BPS showed a molecular weight of 23,434 Da and was abundant in hydroxyl and amino residues. In addition, BPS exhibited a rod-like structure with a rough surface and was dominated by C, N, and O elements. The exopolysaccharide demonstrated remarkable thermal stability, high degradation temperature, and excellent emulsification capacity compared to most reported exopolysaccharides. Moreover, BPS displayed better quenching activities against the four radicals, which provided favorable protection for the strain. Finally, the freezing experiment investigated the cryoprotective effect of BPS on E. coli and S. aureus . BPS effectively improved the cell survival ratio and maintained the activity of Na + /K + -ATPase, which facilitates culture preservation. To the best of our knowledge, our work is the first report suggesting that marine exopolysaccharide has dual-activity. This work presents the foundation for the analysis of the structure and properties of exopolysaccharides produced by deep-sea bacteria.

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Candidate gene analysis of watermelon stripe pattern locus ClSP ongoing recombination suppression - Zhen Yue; Rongxue Ma; Denghu Cheng; Xing Yan; Yaping He; Chunxia Wang; Xiaona Pan; Lijuan Yin; Xian Zhang; Chunhua Wei (Theoretical and Applied Genetics, 2021)

Proteomic analysis of the exosomes secreted from Ctenopharyngodon idellus kidney cells infected with grass carp reovirus reveals their involvement in the cellular responses to viral infection - Xing Zhang; Yunshan Zhang; Jun Pan; Min Zhu; Zi Liang; Zeen Shen; Kun Dai; Bingyu Yan; Yaping Dai; Renyu Xue; Guangli Cao; Xiaolong Hu; et al. (Fish Physiology and Biochemistry, 2021)

Effects of Exogenous Application of GA4+7 and NAA on Sugar Accumulation and Related Gene Expression in Peach Fruits During Developing and Ripening Stages - Xiongwei Li; Pan Liu; Jingyi Zhou; Mingshen Su; Yaping Ma; Huijuan Jia; Jihong Du; Zhongshan Gao; Zhengwen Ye (Journal of Plant Growth Regulation, 2021)

Porphyromonas gingivalis degrades integrin β1 and induces AIF-mediated apoptosis of epithelial cells - Qian Li; Jie Zhou; Li Lin; Haijiao Zhao; Lei Miao; Yaping Pan (Infectious Diseases, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Trends of subtype variation of human immunodeficiency virus type 1 in Zhejiang Province, China - Yaping Yao; Ruolei Xin; Jiezhe Yang; Yun Xu; Jiafeng Zhang; Yan Xia; Xiaohong Pan; Zhihong Guo; Yanhui Song (Virus Genes, 2015)

Mutation screen and RNA analysis disclose the changed splicing of the E-cadherin transcription in gastric cancer - Xiaowei Li; Yafan Gao; Yiyuan Pan; Yan Pan; Lifeng Wang; Nong Xiao; Qiong He; Yimei Fan; Yaping Wang (Familial Cancer, 2013)

Effect of household and commercial processing on acetamiprid, azoxystrobin and methidathion residues during crude rapeseed oil production - Yaping Jiang; Takayuki Shibamoto; Yanjie Li; Canping Pan (Food Additives & Contaminants: Part A, 2013)

Molecular mechanism of elicitor-induced tanshinone accumulation in Salvia miltiorrhiza hairy root cultures - Guoyin Kai; Pan Liao; Hui Xu; Jing Wang; Congcong Zhou; Wei Zhou; Yaping Qi; Jianbo Xiao; Yuliang Wang; Lin Zhang (Acta Physiologiae Plantarum, 2012)

Dissipation of Diethyl Aminoethyl Hexanoate (DA-6) Residues in Pakchoi, Cotton Crops and Soil - Yaping Jiang; Yuting Jiang; Shun He; Heli Zhang; Canping Pan (Bulletin of Environmental Contamination and Toxicology, 2012)

Residue Dynamic of Pyrimorph on Tomatoes, Cucumbers and Soil under Greenhouse Trails - Jing Wang; Lianlian Zhao; Xuesheng Li; Yaping Jiang; Nan Li; Zhaohai Qin; Canping Pan (Bulletin of Environmental Contamination and Toxicology, 2011)

Dissipation and Residues Detection of Dioctyldiethylenetriamine Cetate in Rice Plant and Environment by QuEChERS Method and Liquid Chromatography/Electrospray Tandem Mass Spectrometry - Xuesheng Li; Yaping Jiang; Weili Shan; Canping Pan (Bulletin of Environmental Contamination and Toxicology, 2010)

Spatial distributions of organic carbon and nitrogen and their isotopic compositions in sediments of the Changjiang Estuary and its adjacent sea area - Jianhua Gao; Yaping Wang; Shaoming Pan; Rui Zhang; Jun Li; Fenglong Bai (Journal of Geographical Sciences, 2008)